Perencanaan Jembatan Merangin Menggunakan Sistem Busur Rangka - Anugrah, Fitto Bintang; Suhendra, Suhendra; Dony, Wari (Universitas Batanghari, 2025)
The Merangin Bridge is a national infrastructure located on Jl. Lintas Sumatra, Jambi Province, Merangin Regency which was built during the leadership of President Soeharto in the construction project of the Sumatra cross-Sumatra, more precisely Muarobungo to Sarolangun, in April 1980. From the time span and on April 19, 2025, this bridge appears to have undergone a deformation that makes the bridge swollen, but it is still operating. Therefore, the bridge is planned to use archs using a truss arch system. The planning of this bridge for the loading on the bridge refers to SNI 1725:2016, and the earthquake load of the bridge SNI 2833:2016. In the analysis, the auxiliary program SAP 2000 v.22 is used. From the results of the bridge analysis, 1,000 x 1,000.25 mm box profile steel was used for the upper arch while for the 1,150 x 1,150.25 mm profile box lower arch. The hanger used is a tension rod type with a diameter of 98 mm From the results of the analysis carried out, there was a deflection for the condition of the vehicle's load coupled with an additional dead load and dead load of 170.144 mm. Meanwhile, for the combination of vehicle load plus live or pedestrian load, there was a deflection on the bridge of 78.974 mm, even though both conditions have qualified for deflection on the bridge in accordance with the pedoman persyaratan umum perencanaan jembatan, 2015.